Electrical properties of pre-alloyed Cu-P containing electrically conductive adhesive - Ho, Li Ngee; Tang, Fei Wu; Nishikawa, Hiroshi; Takemoto, Tadashi (Taylor & Francis, 2010)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/